Final report of CARICOM Database Development Project on Education and Training Programme at Tertiary Level Institutions ([s.n.] [S.l.], 2003)
Reports on efforts to build a database on education and training programmes at the tertiary level institutions in selected sectors in order to facilitate the development of the regional accreditation system and the free movement of skills policy of the Single Market and Economy.
Keywords: HIGHER EDUCATION